Keadilan Kontraktual dalam Kebijakan Penghangusan Kuota Internet - Ayu Chairun Nisa (Jurnal Litigasi Amsir, 2026)
This study examines the legal construction of the enforceability of the forfeited quota in the contractual relationship between operators and consumers, as well as legal protection against the policy of forfeiture of the remaining quota from the perspective of civil law. The problem arises from the practice of prepaid internet services that set a certain active period so that the remaining quota cannot be used when the period ends, even though the payment value has been issued by the consumer. This study uses a normative legal method with a legislative approach and an analytical approach to primary, secondary, and tertiary legal materials. The results of the study show that the implementation of the forfeited quota can be formally understood as part of the service, but it must still be subject to the principles of propriety, good faith, transparency, and balance in the agreement. The policy of forfeiture of the remaining quota requires a fairer arrangement so as not to cause unilateral losses to consumers and still provide legal certainty in digital transactions.